Near field communication enabled payment system adoption: A proposed framework - Brohi, Imtiaz Ali; Ali, Najma Imtiaz; Karbasi, Mostafa; Shah, Asadullah; Akbar, Ali; Gharamah, Abdul Rahman; Ali, Asif (IEEE, 2018)
Digital payment system has become essence of todays advanced technological society. Recent promising technology development is Near Field Communication (NFC) that has changed life of consumers in mobile based payment system. NFC is a short range contactless communication technology that has made users life convenient around the world by offering transactions, digital content exchange and connecting electronic devices with a simple touch. Near field communication enabled payment system has been introduced in consumer payment market, interested companies have invested in this technology because of its convenience and security. The purpose of this paper is to propose a conceptual framework in context of developing economies by integrating constructs from Extended Unified Technology Acceptance and Use of Technology (UTAUT2) with some external variables.